Outer limits of the athlete's heart, the effect of gender, and relevance to the differential diagnosis with primary cardiac diseases - Pelliccia, A.; Maron, B. J. (Cardiology Clinics, 1997)
Two concepts from pathologic descriptions of myocardial hypertrophy in trained individuals merit consideration: (1) The heart of the trained athlete can be twice the normal size, but histologic structure remains intact, and (2) the weight of the trained heart does not usually surpass the limit of 500 g, defined as the critical heart weight. Even though this threshold cannot be accepted dogmatically, the concept of an upper limit for physiologic cardiac remodeling is nevertheless relevant to the clinical question of distinguishing extreme expressions of athlete's heart from primary pathologic conditions. This morphologic distinction depends on whether the magnitude of cardiac remodeling in athletes exceeds that expected as a result of athletic conditioning alone. There has also been a great interest in understanding the impact that types of athletic conditioning and gender have on defining the upper limits to which such physiologic hypertrophy may extend.